2023
DOI: 10.3390/ma16052100
|View full text |Cite
|
Sign up to set email alerts
|

First Principles Calculation of Adsorption of Water on MgO (100) Plane

Abstract: The hydration reaction seriously affects the quality and performance of MgO-based products. The final analysis showed that the problem is the surface hydration of MgO. By studying the adsorption and reaction of water molecules on the surface of MgO, we can understand the nature of the problem from the root cause. In this paper, first-principles calculations are performed on the crystal plane of MgO (100) to study the influence of the different orientation, sites and coverage of water molecules on the surface a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 40 publications
1
2
0
Order By: Relevance
“…One involves the Lewis acid-catalyzed intramolecular hydride transfer mechanism of glucose, while the other entails intramolecular proton transfer (from C2 to O5), resulting in the formation of the enediol key intermediate subsequent to the base-catalyzed ring opening of the glucose molecule [14]. In the present study, based on FTIR spectroscopy and other characterizations, it is known that the Mg/Zr-1.0 catalyst is a heterogeneous base catalyst with moderately to weakly basic active sites, and the reaction follows the principle reported by de Bruyn et al Water molecules adsorbed on the surface of the Mg/Zr-1.0 catalyst dissociate and form stable hydroxyl groups on the surface of MgO, which is negatively charged [57]. As a result, glucose undergoes deprotonation at the C2 position when it comes into contact with the catalyst surface, forming an enol intermediate, which enables the catalytic isomerization of fructose by the LdB-AVE mechanism (Scheme 1) [18,23].…”
Section: Plausible Mechanism Of Glucose Isomerization Over Mg/zr-10supporting
confidence: 57%
“…One involves the Lewis acid-catalyzed intramolecular hydride transfer mechanism of glucose, while the other entails intramolecular proton transfer (from C2 to O5), resulting in the formation of the enediol key intermediate subsequent to the base-catalyzed ring opening of the glucose molecule [14]. In the present study, based on FTIR spectroscopy and other characterizations, it is known that the Mg/Zr-1.0 catalyst is a heterogeneous base catalyst with moderately to weakly basic active sites, and the reaction follows the principle reported by de Bruyn et al Water molecules adsorbed on the surface of the Mg/Zr-1.0 catalyst dissociate and form stable hydroxyl groups on the surface of MgO, which is negatively charged [57]. As a result, glucose undergoes deprotonation at the C2 position when it comes into contact with the catalyst surface, forming an enol intermediate, which enables the catalytic isomerization of fructose by the LdB-AVE mechanism (Scheme 1) [18,23].…”
Section: Plausible Mechanism Of Glucose Isomerization Over Mg/zr-10supporting
confidence: 57%
“…In contrast to its ubiquity on Earth and a long history of experimental demonstration in small plants, the details of the hydration mechanism on the surface of MgO remain elusive, and this fact prevents a practical introduction of TCHS technology into the social systems. Since alkaline earth metal oxide has characteristic features in its chemical properties and especially in the interface, various kinds of experimental and computational , research have been reported so far, but the research aimed at the thermochemical application is limited at the present time. …”
Section: Discussionmentioning
confidence: 99%
“…As for computational studies, many calculations have been reported on the physical/chemical properties of MgO due to its unique and interesting character. Most of these calculations discussed the surface properties of the ideal MgO lattice, , since the surface atoms of the MgO lattice were assumed to have potential catalytic activity. Although some previous calculations discussed the surface hydration step on a specific MgO surface, ,, the mechanistic details of the hydration process have not been elucidated until now. Apart from the thermal storage mechanism, Jug and co-workers reported on the water absorption structure on the MgO surface.…”
Section: Introductionmentioning
confidence: 99%